The interaction of achievement goal orientations, self-regulated learning and learning environment in high school science classrooms - Iverach, Michael Robert (Curtin University, 2007)
Despite the substantial amount of education research on “teaching for understanding” and “learning for understanding” processes that has occurred in the fields of achievement goals, constructivist-based pedagogy, motivational beliefs and self-regulated learning there is little research that considers in unison the pillar constructs of these fields. Three studies comprised the present research which was designed to address the proposal that important social- and personal-based constructs associated with achievement goals, constructivist-based pedagogy, motivational beliefs, and self-regulated learning act in an interdisciplinary fashion to influence learning in the high school science classroom. All the large-scale quantitative studies presented a single-level structural equation model that was applicable to the general high school science student, controlling for the variance associated with age, gender, and student type (regular or selective high school student). Results from the two large-scale trait-level correlational studies of Study 1 (n = 655) and Study 2 (n = 617) using the Achievement Goals Questionnaire (Elliot & Church, 1997), Constructivist Learning Environment Survey (Taylor, Fraser, & Fisher, 1997) and the Motivated Strategies for Learning Questionnaire (Pintrich, Smith, Garcia, & McKeachie, 1991) as the main quantitative instruments found support for the hypothesis that a perceived emphasis on the constructivist-based pedagogical dimensions of personal relevance and student negotiation in science classrooms promotes the adoption of mastery-approach and intrinsic value. These analyses also showed the importance of self-efficacy in promoting mastery-approach, performance-approach and the use of regulatory strategies, and that test anxiety had positive associations with mastery-avoidance and performance-avoidance goals.Study 3 comprised of two mini-studies that investigated the associations of competence perceptions, achievement goals and self-regulated learning in two science classroom learning contexts: teacher-led discussion (n = 451) and group work (n = 476). Using specifically developed context-level questionnaires, the results of these studies affirmed current theories concerning the interactions of self-efficacy, achievement goals, self-regulated learning (regulatory strategy use) and maladaptive strategy use. Students interviewed in Study 3 mostly reported the adoption of their achievement goals depended upon personal reasons that were commensurate with current achievement goal theory (Elliot, 1999) rather than specific classroom practices. The present research was also significant in that it tested the empirical stature of two frameworks by which social/cognitive research affiliated with learning environments, achievement goals and self-regulated learning may be conducted. Firstly, the results of the construct validity measures generated across Studies 1, 2 and 3 found support for the existence of the hypothesised 2 X 2 achievement goals framework (Elliot, 1999; Elliot & McGregor, 2001; Pintrich, 2000a). Secondly, the research introduced the tenets of a “context” hypothesis and found support for this perspective throughout the context-level studies. Adjunct multilevel multiple regressions were used in all the quantitative studies to examine the impact of subpopulation variables (age, gender, regular or selective high school student) and multiple goal interactions upon response variables, and to assess the variance attributed to the response variables at the class-level. Implications for the research disciplines studied are presented in terms of teaching practice, theory, future research and research methods.